Fundamental planetary science : physics, chemistry, and habitability - Lissauer, Jack Jonathan, author; De Pater, Imke, 1952-, author (New York, USA : Cambridge University Press, 2013)
"A quantitative, broad-based introduction to planetary systems science for advanced undergraduate students, including planet formation, extrasolar planets, and planetary habitability"--provided by publisher